(untitled) (Journal of Academic Research, 2018)
The mono oxime of the acetyl acetone 4 was synthesized through a solvent-free procedure yielding only 27% of E/Z isomeric mixture in a ratio of (9:1). The benzoyl ester of this oxime was also obtained in 49% yield and formed in two isomeric conformations Z/E in a ratio of (9:1). The MM2 molecular mechanics method showed, as expected, that the E-isomer of the mono oxime 4 I was the favored to be formed as it has the lower total energy than the Z-isomer 4 II. However, the MM2 method predicted unexpectedly that the Z-isomer of the benzoyl ester 6 IV has a lower total energy than its counterpart E-isomer 6 III.